SUSTAINABLE TOURISM DEVELOPMENT IN CAN THO CITY: A QUALITATIVE APPROACH - Le Thi Dieu Hien; Nguyen Quoc Nghi; Le Thi Khanh Duy (International Journal Management and Economic, 2026)
Aiming to propose solutions for sustainable tourism development in Can Tho City, this study has adopted a qualitative approach to clarify key bottlenecks in the city’s tourism sector that hinder sustainability. Through focus group discussions and expert consultations, the study has identified bottlenecks related to economic benefits, environmental and tourism resources, and socio-cultural aspects. Based on these findings, the study has proposed several solutions to promote sustainable tourism in Can Tho City, including ensuring fair economic benefit distribution, protecting the environment and tourism resources, and preserving community culture.